PEMAHAMAN WALI BAPTIS TENTANG PERAN DAN TANGGUNG JAWAB SERTA PELAKSANAANNYA - Pratiwi, Maria Valentina Putri; Ardijanto, Don Bosco Karnan (CREDENDUM: Jurnal Pendidikan Agama, 2020)
This study aims to understand the godparents' comprehension of their roles and responsibilities, identify the implementation of these roles and responsibilities at St. Peter Station, Warujayeng, and examine the challenges and strengths they encounter in fulfilling their duties. The research was conducted at St. Peter Station, Warujayeng, using a qualitative method. The findings indicate that godparents serve as spiritual parents responsible for guiding, nurturing, and fostering the faith of their baptized children. They fulfill their roles and responsibilities before, during, and after the sacrament of baptism, although they face various challenges, both internal and external, in the process.